OPTIMASI MULTIRESPON PADA PROSES 3D PRINTING MATERIAL PLA DENGAN METODE TAGUCHI GREY - Ronaldo Febrian; Yopi Yusuf Tanoto; Vincensius Filbert; Nicholas Adriel (Jurnal Rekayasa Mesin, 2022)
The use of manufacturing additives or commonly known as 3D Printing is increasingly widespread. The type of additive manufacturing that is often used is FDM (Fused Deposition Modeling). The most frequently used filament for prototyping and research is PLA (Poly Lactide Acid) type filament. This research will use multiresponse optimization, namely Taguchi-grey. So that later in this study will use 9 conditions with 3 parameters and 3 levels. The parameters used were orientation (0 °, 45 °, 90 °), nozzle temperature (190 °C, 200 °C, 220 °C), and bed temperature (0 °C, 30 °C, 60 °C). The purpose of this study was to find the most optimal parameters based on response time, dimensional accuracy and tensile strength. Based on analysis using Taguchi-grey, ANOVA results show that the most significant contribution is nozzle temperature (51%) and orientation (42%). From ANOVA, it can be seen that the most optimal condition is condition 6 which has been printed, with orientation of 45°, nozzle temperature of 220°C and bed temperature of 0°C.